(untitled) (مجلة جامعة اللاذقية - سلسلة العلوم الأساسية, 2013)
درسنا في هذا البحث بعض خواص أسرة واسعة من المنحنيات والتي تسمى k- منحنيات، والتي تعرف من خلال : وجود علاقة بين أطوال الأقواس والأوتار التي تصل بين أية نقطتين منها بشكل خاص درسنا تأثير بعض التحويلات في منحنيات هذه الأسرةومن ثم درسنا تقريب صف دوال هولدر الموزن المعرفة على أسرة المنحنيات – k We study in this research some properties of wide class of curves, called k-curves, which is defined by a relation existing between arches and chords connecting any two arbitrary points on it Especially we study the effect of some mappes on the curves of this class. Then we study the approximation of weighted Holder class of function on k-curves